Board of Governors' Hot Topic 2014: Will Fee for Service Survive?. (2nd September 2014) - Parikh, Sanjay R.; Kennedy, David W.; Waguespack, Richard W.; Denneny, James C.; Setzen, Michael
Abstract : Program Description: On the hinge of health care reform, the Board of Governors' (BOG's) 2014 hot topic is: will fee for service survive? Expert panelists, consisting of American Academy of Otolaryngology—Head and Neck Surgery presidents, BOG chairs, and physician payment and policy workgroup members, will discuss if fee for service will be superseded by payments based on work relative value units, quality measures, hospital employment, and bundled payments. Presentations will be made on current and past payment structures, bundled payments, quality metrics, and the sustainability of private practice. Time for interaction between the audience and panelists will be ensured through a final round table discussion. Educational Objectives: (1) Describe the history of fee for service and how it has changed in the past 10 years. (2) Relate the impact of health care reform on current and future payment systems. (3) Recognize the challenges private practice will have with new reimbursement models.